The nucleotide sequence surrounding the replication terminus of R6K. - Bastia, D (1981)
The replication terminus of the plasmid R6K has been cloned into the single-stranded DNA phage vector M13mp5 and also into the plasmid vectors pBR313 and PBR322. By using single-stranded DNA templates prepared from the recombinant DNA clones, the sequence of 215 base pairs of DNA containing the replication terminus has been determined. The DNA sequence of the region of the terminus does not contain any 2-fold rotational symmetry. Therefore, folding of the DNA at the region of the terminus is unlikely to be a cause for replication termination. Interaction of a host-specified protein(s) with the sequence of the replication terminus is probably the basis of the mechanism of replicaion termination.